Critical Rhythm The Poetics of a Literary Life Form - Glaser, Ben; Culler, Jonathan (Fordham University Press, 2019)
Explores both the theory and practice of rhythm in literature with a focus on nineteenth and twentieth-century poetry. Emphasis on rhythm's role in contemporary literary criticism, including debates about poetic form and genre.This collection intervenes in recent debates over formalism, historicism, poetics, and lyric by focusing on one of literary criticism's most important, most vested, and perhaps least well-defined or definable terms. Rhythm in these essays is at once a defamiliarizing aesthetic force and an unstable concept. It is a key term through which Romantic, Modern, and contemporary literary theory define form, either in conversation with or opposition to meter. It has rich but also problematic roots in still-lingering nineteenth-century notions of primitive, oral, communal, and sometimes racialized poetics. But there are reasons to understand and even embrace its seductions, including its resistance to lyrical voice if not identity as such.